Digital Literacy Competence: Learning Environment and Parental Support for Vocational High School Students' Learning Motivation - Wahdania Wahdania; Anas Arfandi; Sanatang Sanatang (ETDC: Indonesian Journal of Research and Educational Review, 2026)
In the era of digital transformation, vocational high school students must possess strong learning motivation to master essential technical competencies. However, fluctuations in motivation are often driven by how effectively students manage digital literacy, utilize their learning environment, and receive moral support from their families. This study aims to analyze the levels of digital literacy competence, learning environment utilization, parental support, and learning motivation among vocational high school students, while examining the partial and simultaneous influences of these factors on motivation. Employing a quantitative approach with an ex post facto design, the research sampled 150 11th-grade Computer and Network Engineering students from three public vocational schools in Makassar City, selected via proportional random sampling. Data were collected using validated Likert-scale questionnaires and analyzed through descriptive and associative regression techniques. Findings indicate that all variables—digital literacy, learning environment, parental support, and learning motivation—fall within the high to very high categories (65%–80%). Partially, digital literacy (R2=0.585), learning environment (R2=0.262), and parental support (R^2=0.575) significantly affect motivation. Simultaneously, these variables contribute 71.7% to learning motivation (F_count=123.423 > F_table=2.67), with parental support emerging as the most dominant factor (β=0.781). This study underscores that enhancing vocational motivation requires a synergy between digital proficiency and active parental involvement. Consequently, schools should develop integrated digital literacy programs that foster stronger parental participation to optimize student engagement.